Detection of building features in interferometric synthetic aperture radar datasets / Ahmad Sanusi Che Cob - Che Cob, Ahmad Sanusi (Institute of Graduate Studies, UiTM, 2018)
Building features are the main components of geospatial data which are constantly required for many applications in this ever changing world. Producing and consistently updating building layers have been the functions of many mapping organisations in the world including Malaysia. In this regard, The Department of Survey and Mapping Malaysia (JUPEM) has faced an uphill task to frequently establish the building layers throughout the country where persistence cloud cover has always been the big issue. An alternative solution would be to utilize Synthetic Aperture Radar Interferometry (InSAR) technology which is widely known to have the penetration capabilities through cloud cover to perform such task. This study investigates the potential of using interferometric SAR datasets products namely unwrapped phase images and digital surface models (DSM) as the main input for building features detection strategy of built up area in Tanjung Malim district, State of Perak in Peninsular Malaysia. The objectives of the research are to improve the method of building features extraction from InSAR dataset by using shape and size of structure elements and to combine the extracted building features with the generated DSM height models to create 3D building model. The last objective is to make an assessment of 3D building features model which are derived from interferometric products with Photogrammetric-based DSM (PhotoDSM) and the digitised vector map data from JUPEM. In the first part, the study adopted commercial off the shelf (COTS) software Erdas Imagine 2011 and Fast Fourier Transformation-based IDL program to obtain digital surface model without the availability of ground control points (GCP) and secondly for building footprint detection, image filtering technique of ENVI and IDL involving convolution and morphological operation were used…